Serum levels of neopterin, inflammatory markers and oxidative stress indicators in hyperemesis gravidarum - Tunc, Senem Yaman; Agacayak, Elif; Budak, Sukru; Tunc, Nurettin; Icen, Mehmet Sait; Findik, Fatih Mehmet; Gul, Talip (Wiley-Blackwell, 2016)
Aim: To investigate whether serum levels of neopterin and inflammatory markers including C-reactive protein (CRP), tumor necrosis factor-alpha (TNF-alpha), interleukin-6 (IL-6) and oxidative status indicators were altered in patients with hyperemesis gravidarum (HG) compared to asymptomatic pregnant women. Methods: This cross-sectional study was performed including 30 pregnant women with HG (mean age: 30.67 +/- 6.68) and 30 asymptomatic pregnant women (mean age: 28.00 +/- 5.30). Demographic features, obstetric history, and the Pregnancy Unique Quantification of Emesis/Nausea (PUQE) index were noted. Complete blood count, serum biochemical assay and measurement of CRP, TNF-alpha, IL-6, total antioxidant status and total oxidative status (TOS) levels were taken and compared between groups. Results: White blood cell count (P = 0.013), platelet count (P = 0.015), TOS (P < 0.001), and PUQE score (P < 0.001) were remarkably higher in HG pregnancies. On the other hand, serum levels of lactate dehydrogenase, (P < 0.001), sodium (P < 0.001), potassium (P < 0.001), chloride (P < 0.001) and TAS (P < 0.001) were higher in the control group. There was no difference in the levels of neopterin, CRP, TNF-alpha and IL-6. In patients with HG, a positive correlation was detected between TOS and serum levels of lactate dehydrogenase, while TNF-alpha, IL-6 and neopterin were positively correlated with hemoglobin levels. Conclusion: Our results demonstrated no association between inflammation and HG. Elucidation of the pathophysiology and complex interaction between various inflammatory processes in HG necessitates further trials on larger series.
Keywords: cytokine; hyperemesis gravidarum; inflammation; neopterin; oxidative stress